"An Englisman in Denmark": What I have learned from Dansk musikterapi [Danish music therapy] - Wigram, Tony (Voices: A World Forum for Music Therapy, 2011)
This is an article originally published in a danish book celebrating the 25th anniversary for the music therapy training course at the Aalborg University: Ridder, H.M. (Ed.) Musikterapiuddannelsen 25 år. Festskrift. Aalborg: Aalborg Universitet, s. 47-50. It is republished here with the kind permission from the publisher.